Effects of Gender on Basic Numerical and Arithmetic Skills: Pilot Data From Third to Ninth Grade for a Large-Scale Online Dyscalculia Screener - Räsänen, Pekka; Aunio, Pirjo; Laine, Anu; Hakkarainen, Airi; Väisänen, Eija; Finell, Jonatan; Rajala, Teemu; Laakso, Mikko-Jussi; Korhonen, Johan (Frontiers in Education, 2021)
In this study, we analyzed the effects of gender on basic number skills from 3rd to 9th grade in Finland. Because the international comparison studies have shown slightly different developmental trends in mathematical attainment for different language groups in Finland, we added language of education as a variable into our analysis. Participants were 4265 students from 3rd to 9th grade in Finland representing students in two national languages (Finnish, n = 2833, and Swedish, n = 1432) First, confirmatory factor analyses showed that the subtasks in the dyscalculia screener formed two separate factors; number processing skills and arithmetic fluency. Secondly, we found a linear development trend across age cohorts in both factors. Third, reliability and validity evidence of the measures supported the use of these tasks in the whole age group from 9 to15 years. First, we found an increasing gender difference in favor of girls and Swedish speaking students by grade level in number processing skills, while boys showed a better performance and a larger variance in tasks measuring arithmetic fluency. The results indicate that the gender ratio within the group with mathematical learning disabilities depends directly on tasks used to measure their basic number skills.